1995
DOI: 10.1111/j.1479-828x.1995.tb02145.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Timing of Obstetric Ultrasound in Victoria 1991–1992: a Population‐based Study

Abstract: A statewide study to ascertain the number of ultrasound scans received by women in pregnancy, to identify the proportion having a scan at 16 to 20 weeks' gestation, and to establish where the scan at 16 to 20 weeks was performed was carried out between January, 1991 and June, 1992 in Victoria. Additional data were collected by midwives and entered on the perinatal morbidity statistics form routinely completed for all births. Of 52,319 women providing responses, 3.1% did not have a scan. Of the remaining 96.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Rushworth et al , 12 found that among New South Wales residents who made national health insurance claims for antenatal care in 1990, 94% of women had ultrasound scans and approximately 75% were before 20 weeks of gestation. A study in Victoria found similar results for 1991–1992 13 . Determination of gestational age by ultrasound is more accurate earlier in pregnancy than later because fetal size varies less 10,14 .…”
Section: Discussionmentioning
confidence: 70%
“…Rushworth et al , 12 found that among New South Wales residents who made national health insurance claims for antenatal care in 1990, 94% of women had ultrasound scans and approximately 75% were before 20 weeks of gestation. A study in Victoria found similar results for 1991–1992 13 . Determination of gestational age by ultrasound is more accurate earlier in pregnancy than later because fetal size varies less 10,14 .…”
Section: Discussionmentioning
confidence: 70%
“…The estimates are that around 96.9% of pregnant women in Victoria during this period had at least one ultrasound scan and 73.5% had 16-to 10-week ultrasound. 9 Multiple pregnancies and cases with birth defects were excluded to avoid confounding. Birth defect is any abnormality of prenatal origin, either present at conception or occurring before the end of pregnancy.…”
Section: Data Sourcementioning
confidence: 99%
“…In Victoria, 97% of women have at least one antenatal ultrasound, most of which occur at <20 wks' gestation (13). If there was a discrepancy between the best obstetric estimate of gestation and a pediatric assessment after birth of more than 2 wk, the pediatric estimate was taken to be correct.…”
Section: Measurementsmentioning
confidence: 99%